Duloxetine Increases Serotonin and Norepinephrine Availability in Healthy Subjects: A Double-Blind, Controlled Study - Chalon, Stephan A; Granier, Luc-André; Vandenhende, François R; Bieck, Peter R; Bymaster, Frank P; Joliat, Melissa J; Hirth, Christine; Potter, William Z (Neuropsychopharmacology (New York, N.Y.), 2003)
Evidence suggests that compounds that increase the synaptic availability of more than one neurotransmitter have greater efficacy in the treatment of depression than single-acting drugs. Preclinical studies indicate that duloxetine acts to inhibit serotonin (5-HT) and norepinephrine (NE) transporters. The ability of duloxetine to alter 5-HT and NE reuptake was tested in 12 healthy male subjects. Placebo, desipramine 50 mg b.i.d., and duloxetine (80 mg q.d. or 60 mg b.i.d.) were compared in a randomized, double-blind, three-period crossover study in 12 healthy male subjects. Whole-blood 5-HT, urinary excretion of NE and major metabolites, and TYR PD 30 (IV tyramine pressor dose needed to increase systolic blood pressure by 30 mmHg) were measured at steady state. Vital signs were measured periodically. Duloxetine affected 5-HT reuptake, with whole-blood 5-HT depletion vs placebo (80 mg q.d.: p =0.07; 60 mg b.i.d.: p =0.02; combined regimens: p =0.01). Cardiovascular changes reflecting increased sympathetic tone were observed with both duloxetine and desipramine, and both treatments significantly decreased whole body NE turnover ( p <0.01). Duloxetine and desipramine were associated with similar mean increases in fractional extraneuronal NE concentration, although these changes did not reach statistical significance. TYR PD 30 increased significantly with desipramine dosing ( p <0.01). In conclusion, whole-blood measurements confirm that duloxetine inhibits platelet 5-HT uptake in vivo . Urinary and cardiovascular measurements suggest that duloxetine has an effect on NE synthesis and turnover, indicative of NE reuptake inhibition. The lack of a detectable impact of duloxetine on TYR PD 30 suggests that this may not be the most sensitive indirect measure of NE reuptake when assessing dual reuptake inhibitors.